(untitled) (Journal of the College of Basic Education, 2024)
The subject of climate change occupies an important place in modern studies because of its importance and direct or indirect connection to human life and living organisms. Climate change is not limited to temperatures and their increase, but rather extends to most of the climate elements and phenomena. Temperatures and other climate elements are the result of a change in what The atmosphere is now an integrated and interactive system, and the effect that occurs in every place can be transmitted to another place. The maximum temperature is important because it represents the highest temperature rise of the day, became clear from the study that the impact of climate change is very significant in increasing the average maximum temperatures during the fall months. In the first cycle (1973-1982), the average maximum temperature for the months of September, October and November reached (40.3 - 33 - 23.7). Celsius respectively, with a standard deviation of (2.26 - 2.07 - 2.28), and in the second cycle (1983-1992), where it recorded (39.8 -32.7 -24.1) Celsius, with a standard deviation of (2.21 - 2.50 - 2.37) respectively, and in the third cycle (1993-2002) it recorded (40.2 - 34.7 - 24.8) C with a standard deviation of (2.46 - 2.76 - 1.84), and in the fourth cycle (2003 - 2012) Humidity rates reached (40.4 -34.4 -24.4) C with a standard deviation of (2.18 - 2.75 - 2.13) respectively, and in the fifth cycle (2013-2022) rates were recorded at (42.5 -36.8 - 25.2) C with a standard deviation of (2.32 - 3.35 - 1.95), respectively, and the amount of deviation from the general average varied at each station in the study area.